Rancang Bangun Pemarut Kulit Markisa - Dian Rahmawati; Pranowo Sidi; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Fruit skin as a leftover ingredient that is abundant and in general has not been widely used. The general public does not yet know the benefits of passion fruit skin. One of them can be used as jam, by smoothing it first using a blender. Due to the hard nature of passion fruit skin, the knife orblender becomes damaged. Therefore, a passion fruit skin grater was designed. The method used by the author is the Ulrich method by selecting several design concepts, designing aided by CAD software for making drawings, fabrication, assembling machine components, and testing tools todetermine the production results of the machine. There are various types of materials used in the manufacture of passion fruit leather grater machines, starting from the frame and engine mount using L profiles with ASTM A36 material, grating cover and hopper using SS 304 material, pulley cover using aluminum material, the shaft on this machine uses S45C material, and wear 1 V-belt with rubber material. This machine uses a 1 HP 1 phase electric motor. After being tested, it was produced grated passion fruit skin with an average fiber dimension ± 0.5 cm.This passion fruit grater machine has a capacity of 3 kg / hour.